Walter Kälin on the outlook for IDPs - Walter Kälin (Forced Migration Review, 2011)
Walter Kälin served for six years as the UN Secretary-General’s Representative on the Human Rights of IDPs. We publish his reflections on those six years and the future for IDPs…